Irritative potency of selected wound antiseptics in the hen's egg test on chorioallantoic membrane to predict their compatibility to wounds. Issue 2 (5th December 2018) - Harnoss, Julian Camill; Elrub, Qasim Mahmoud Abu; Jung, Jin‐On; Koburger, Torsten; Assadian, Ojan; Dissemond, Joachim; Baguhl, Romy; Papke, Roald; Kramer, Axel; ,
ABSTRACT: Antiseptics are being used for prevention of infections in acute wounds and for treatment of infections in acute and chronic wounds. However, some antiseptics' high tissue toxicity might delay the healing process. The aim of this study was to investigate the tissue toxicity of preferentially used wound antiseptics and the influence of antiphlogistic additives via the hen's egg test on the chorioallantoic membrane (HET‐CAM). The HET‐CAM is a semi‐in‐vivo method testing the tissue tolerability of wound antiseptics by evaluating the blood vessel reaction of the chorioallantoic membrane in terms of hemorrhage, vessel lysis, and coagulation. For each test day, selected test substances were applied on the membranes of two to three eggs according to the test protocol. The overall irritation was then evaluated by referring to a calculated score. Normal distribution of the resulting scores was confirmed by D'Agostino‐Pearson omnibus K2 test. Significant differences between the antiseptics were calculated by Tukey's multiple comparisons test. Severe CAM reactions were observed after short‐term application of octenidine based wound gel (0.05%) and chlorhexidine digluconate (0.5% solution), moderate reactions for octenidine (0.05%) in aqueous solution combined with dexpanthenol (1.34%) and allantoin (0.2%) or for hydrogen peroxide (1.5% and 0.5%) in aqueous solution, slight reactions were observed for hydrogen peroxide (1.5%) in aqueous solution in combination with sodium thiocyanate (0.698%) and for the combination of NaOCl/HOCl (each 0.004%). Polyhexanide (0.04%) in Ringer solution and polyhexanide (0.05%) in Lipofundin, the hemoglobin spray (10%), dexpanthenol, and allantoin showed no irritation. The HET‐CAM qualifies as a primary screening test for tissue tolerance of wound antiseptics. Regarding local tolerability, polyhexanide and hypochlorite are superior to other antiseptics.